High level efficacy of lufenuron against sea lice (Lepeophtheirus salmonis) linked to rapid impact on moulting processes. Issue 2 (August 2018) - Poley, Jordan D.; Braden, Laura M.; Messmer, Amber M.; Igboeli, Okechukwu O.; Whyte, Shona K.; Macdonald, Alicia; Rodriguez, Jose; Gameiro, Marta; Rufener, Lucien; Bouvier, Jacques; Wadowska, Dorota W.; Koop, Ben F.; et al.
Abstract: Drug resistance in the salmon louse Lepeophtheirus salmonis is a global issue for Atlantic salmon aquaculture. Multiple resistance has been described across most available compound classes with the exception of the benzoylureas. To target this gap in effective management of L. salmonis and other species of sea lice (e.g. Caligus spp.), Elanco Animal Health is developing an in-feed treatment containing lufenuron (a benzoylurea) to be administered prior to seawater transfer of salmon smolts and to provide long-term protection of salmon against sea lice infestations. Benzoylureas disrupt chitin synthesis, formation, and deposition during all moulting events. However, the mechanism(s) of action are not yet fully understood and most research completed to date has focused on insects. We exposed the first parasitic stage of L. salmonis to 700 ppb lufenuron for three hours and observed over 90% reduction in survival to the chalimus II life stage on the host, as compared to vehicle controls. This agrees with a follow up in vivo administration study on the host, which showed >95% reduction by the chalimus I stage. Transcriptomic responses of salmon lice exposed to lufenuron included genes related to moulting, epithelial differentiation, solute transport, and general developmental processes. Global metabolite profiles also suggest that membrane stability and fluidity is impacted in treated lice. These molecular signals are likely the underpinnings of an abnormal moulting process and cuticle formation observed ultrastructurally using transmission electron microscopy. Treated nauplii-staged lice exhibited multiple abnormalities in the integument, suggesting that the coordinated assembly of the epi- and procuticle is impaired. In all cases, treatment with lufenuron had rapid impacts on L. salmonis development. We describe multiple experiments to characterize the efficacy of lufenuron on eggs, larvae, and parasitic stages of L. salmonis, and provide the most comprehensive assessment of the physiological responses of a marine arthropod to a benzoylurea chemical. Graphical abstract: Image 1 Highlights: Lufenuron is a new treatment for sea lice control in salmon aquaculture. A 96% reduction in sea lice was observed in salmon fed lufenuron. Salmon lice exposed to lufenuron have deformed cuticles. Transcriptomics and metabolomics suggest that lufenuron inhibits chitin transport, organization, and/or abundance. Novel genes related to sea lice development were discovered.